2011
DOI: 10.1080/15377903.2011.590777
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Leukemia Survivors and Their Return to School: A Literature Review, Case Study, and Recommendations

Abstract: Leukemias (blood cell cancers) and central nervous system tumors are the most frequently occurring types of cancer in children. Mortality rates from all childhood cancers have decreased over the past 2 decades. As a result, many childhood cancer survivors are now returning to their schools after having been successfully treated. Although most of these survivors will continue receiving ongoing medical management after cancer treatment, far fewer receive specialized educational services. The purpose of this arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 69 publications
(98 reference statements)
1
12
0
1
Order By: Relevance
“…Three reviews (two high quality) examining cancer that included 15 original articles found evidence for both positive and challenging school reintegration experiences (Wakefield et al ; Herrmann et al ; Pini et al ). School reintegration was not examined in other illnesses.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three reviews (two high quality) examining cancer that included 15 original articles found evidence for both positive and challenging school reintegration experiences (Wakefield et al ; Herrmann et al ; Pini et al ). School reintegration was not examined in other illnesses.…”
Section: Resultsmentioning
confidence: 99%
“…School practices promoting students' engagement with school may be a viable support approach that addresses the academic and social needs of students with chronic illness. Two high-quality systematic reviews (Vance & Eiser 2002;Wakefield et al 2010) and one narrative review (Herrmann et al 2011) (case-controlled, cohort and qualitative studies)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Нейрокогнитивные нару-шения вызывают ограничения в ежедневной активно-сти: в самообслуживании, учебе, профессиональной деятельности [5,9,10].…”
unclassified